(untitled) (International Journal of Physiotherapy, 2017)
Background: Polyneuropathy is one of the most common chronic complications associated with diabetes mellitus, it is a damage to the peripheral nerves and manifested by signs and symptoms as numbness, irritation, and pain in the upper and lower limbs. This study aimed to evaluate muscular performance and proprioception at the ankle in diabetic neuropathic patients with quantitative and standardized tools and correlate these findings with those of sural nerve conduction velocity (sural NCV) and amplitude. Methods: Fifteen male patients with diabetic neuropathy participated in this study, with age ranged from 40 to 55 years, and fifteen age-matched healthy subjects participated as a control group. Biodex Isokinetic System was used to assess the strength of ankle dorsiflexors and planter flexors and ankle reposition accuracy. Berg balance test was used to assess balance. Sural nerve conduction velocity (NCV) and amplitude were examined by diabetic polyneuropathy check (DPN-check) device. Results: The results showed a significant decrease in the mean peak torque values of the plantar flexors and dorsiflexors and a significant increase in the reposition error in the diabetic neuropathic group (p=0.0001). The results also revealed a significant decrease in the mean values of the Berg balance scores in diabetic neuropathy group (p=0.0001). Sural NCV and amplitude tests revealed abnormal values (p<0.05). Conclusion: It was concluded that the isokinetic system is an objective and sensitive tool to detect the motor and sensory changes of the diabetic neuropathic patients, also an examination by DPN-check device help in the determination of the severity of the disease. Moreover, it can be concluded that there are strong correlations between duration of diabetes and sural nerve NCV and amplitude and the peak torque of the muscles around the ankle.